Peran Storytelling Influencer dalam Membangun Kepercayaan dan Citra Positif Produk Halal: Studi Kasus Fadil Jaidi - Elsa Syahrika Salmaria; Sulistyowati, Sulistyowati; Moh Firdaus Faiz Al’Ula; Siti Nurun Nadhifa (MANABIS: Jurnal Manajemen dan Bisnis, 2025)
The growth of social media has changed how halal products are promoted in the digital era. Marketing strategies are no longer focused only on advertising but also on storytelling that can create emotional connections with consumers. This study aims to explain the role of storytelling influencers in building trust and a positive image of halal products, using Fadil Jaidi as a case study of a Muslim influencer in Indonesia. The research uses a descriptive qualitative method by analyzing Fadil Jaidi’s social media content related to halal product promotion and reviewing literature on marketing communication and ethical promotion. The results show that Fadil Jaidi’s storytelling style, which combines honesty, humor, and social awareness, helps increase consumer trust and strengthen the positive image of halal brands. This approach also reflects ethical values and social responsibility that align with Environmental, Social, and Governance (ESG) principles. Therefore, influencers play an important role in conveying moral values and building a positive image of halal products in the growing world of digital marketing.